Cadcom, software para el diseño de radioenlaces. Fundamentos - Gómez, Juan Carlos; Gonzáles, Germán H; Quiroga, Jorge E (Ingeniería, 2000)
The design of radiolinks as much lands as satellites involves such quantity of entry variables (datas and designs criterions), steps (equations for the calculation of differents parameters) and starting variables (results), that necessarily obligate to designer to do use of some automatic tool of design, still more if by to obtain the finale design we require to evaluate differents alternatives.